The Assessment of the frequency and level of suicide risk in patients with schizophrenia presenting at a tertiary care hospital - Badar, Ammarah; Taufique, Fatima; Lal, Chooni; Jat, Ilyaas; Suleman, Fawad; Kumar, Anil (Journal of Pakistan Psychiatric Society, 2021)
Objective: To determine the frequency and level of suicide risk in patients with schizophrenia presenting at a tertiary care hospital.Study Design: Cross sectional descriptive studySetting: Department Of Psychiatry and Behavioral Sciences, JPMC, Karachi, Pakistan.Subjects: Two hundred previously diagnosed cases of Schizophrenia, including males and females, 18 years and above by age, were enrolled. Patients with mental retardation and post-schizophrenic depression were excluded to control the confounding factors.Methods: Patients were enrolled through consecutive purposive sampling. “California Risk Estimator for Suicide” was used to assess the outcome variables. Data was analyzed through SPSS version 17. P-value <0.05 was taken as significant. Ethical issues were addressed according to the IRB of the institute.Results: Majority of patients were males, 18 to 29 years old, single, matriculate, having schizophrenia for less than five years. Almost equal proportion of patients had “low”, “moderate” and “high” severity of suicide risk, signifying a huge amount of suicide risk as compared to general population. The socio-demographic factors had a significant Impact.Conclusion: Patients with schizophrenia have significant risk of suicide. Hence, every patient must be assessed thoroughly for suicide risk. The bio-psycho-social model of health care is the key to success.